Handbook of corporate equity derivatives and equity capital markets - Ramirez, Juan, 1961- (Chichester, West Sussex : Wiley, 2011)
'Equity strategies are closely guarded secrets and as such, there is very little written about how investors and corporate can utilise equity vehicles as part of their growth strategies. In this much-needed book, industry expert Juan Ramiraz guides readers through the whole range of equity derivative instruments, showing how they can be applied to a range of equity capital market situations, including hedging, yield enhancement and disposal of strategic stakes, mergers and acquisitions, stock options plan hedging, equity financings, share buybacks and other transactions on treasury shares, bank regulatory capital arbitrage and tax driven situations. The book includes case studies to highlight how equity derivative strategies have been used in real-life situations'--
Machine generated contents note: Preface.About the Author.1. Main Strategic Equity Derivative Instruments.1.1 Equity Forwards.1.2 Equity Swaps.1.3 Stock Lending and Borrowing.1.4 Call and Put Options.1.5 Dividend Swaps.1.6 Variance Swaps and Volatility Swaps.2. Equity Capital Markets Products.2.1 Main Equity Capital Markets Products.2.2 Initial Public Offerings.2.3 Cast Study: Google's Dutch Auction IPO.2.4 Rights Issues (or Rights Offerings).2.5 Rights Issues of Convertible Bonds.2.6 Accelerated Book-buildings.2.7 At the Market Offerings.3. Convertible Bonds and Mandatory Convertible Bonds.3.1 Introduction to Convertible Bonds.3.2 Who Buys Convertible Bonds?3.3 Convertible Bonds: The Issuer Perspective.3.4 Cast Study: Infineon's Convertible Bond.3.5 Delta Share Repurchase Strategy.3.6 Mandatory Convertible Bonds.3.7 Rationale for Issuing Mandatory Convertibles.3.8 Rationale for Investing in Mandatory Convertibles.3.9 Fixed Parity Mandatory Convertibles.3.10 Variable Parity Mandatory Convertibles.3.11 Dividend Enhanced Convertible Securities.3.12 Case Study: UBS's DECS.3.13 Special Clauses in Convertibles.3.14 Contingent Convertibles: FRESHES, CASHES and ECNS.4. Strategic Equity Transactions around Convertible/Exchangeable Bonds.4.1 Issuing and Exchangeable with a Third-party Guarantee.4.2 Issuing a Convertible Bond through a Third Party.4.3 Crystallizing a Gain in a Convertible Investment through Warrants.4.4 Monetizing a Stake with an Exchangeable Plus a Put.4.5 Increasing Likelihood of Conversion with a Call Spread.4.6 Decreasing Likelihood of Conversion with a Call Spread.4.7 Double Issuance of Exchangeable Bonds.4.8 Buying Back Conversion Rights.4.9 Buying Back Convertible/Exchangeable Bonds.4.10 Pre-IPO Convertible Bonds.5. Hedging and Yield Enhancing Strategic Stakes.5.1 Hedging a Strategic Stake.5.2 Yield Enhancement of a Strategic Stake.6. Disposal of Strategic Stakes.6.1 Most Common Disposal Strategies.6.2 Deterministic Disposal Strategies.6.3 Enhanced Disposal Strategies.6.4 Derecognition Strategies.6.5 Combination of ARB and a Call Option/Exchangeable.7. Strategic Equity Derivatives in Mergers and Acquisitions.7.1 Keeping Voting Rights in Proxy Contests.7.2 Submitting Resolutions to a AGM.7.3 Increasing Likelihood of Success of a Merger Arbitrage Position.7.4 Avoiding Mandatory Offer Rules.7.5 Increasing Likelihood of Success of a Takeover.8. Stock Options Plan Hedging.8.1 Main Equity-based Compensation Plans.8.2 IFRS Accounting for Equity-based Compensation Plans.8.3 Case Study: ABC's ESOP and SAR.8.4 Main ESOP/SAR Hedging Strategies.8.5 HSBC'S Performance Share Plan.9. Equity Financings.9.1 Cast Study: Equity Collateralized Bond.9.2 Sale + Equity Swap.9.3 Prepaid Forward + Equity Swap + Pledge.9.4 Repo Financing.9.5 Stock Loan Financing.9.6 Put Financing.9.7 Collared Financing.9.8 Revolving Margin Loan Facilities.10. Share Buybacks and Other Transactions on Treasury Shares.10.1 Open Market Repurchase Programs.10.2 Accelerated Repurchase Programs.10.3 VWAP-linked Repurchase Programs.10.4 Prepaid Collared Repurchase Programs.10.5 Deep-in-the-money Call Purchase.10.6 Asian Call Purchase.10.7 Publicly Offered Repurchase Programs.10.8 Public Offer of Put Options.10.9 Private Sale of a Put Option.10.10 Acquisition of Shares with a Range Accrual.10.11 Other Transactions on Treasury Shares.11. Bank Regulatory Capital.11.1 An Overview of Basel III.11.2 Tier 1 Capital.11.3 Tier 2 Capital.11.4 Deductions from Common Equity Tier 1 Capital.11.5 Other Capital Buffers.11.6 Transitional Arrangements.11.7 Leverage Ratio.11.8 Liquidity Coverage Ratio.11.9 Net Stable Funding Ratio.11.10 Case Study: Calculation of Minority Interests.11.11 Case Study: Creating Minority Interests.11.12 Case Study: Reducing Risk Weighting.11.13 Case Study: Releasing Common Eqiity.11.14 Case Study: Reducing an Unconsolidated Financial Stake.11.15 Case Study: Commerzbank's Capital Structure Enhancement with Creditu Suisse.12. Tax-Driven Strategic Equity Transactions.12.1 An Overview of Tax-driven Strategic Equity Opportunities.12.2 Dividend Arbitrage.12.3 Dividends vs. Interest Arbitrage.12.4 Capital Gains vs. Derivatives Losses Arbitrage.12.5 Corporate Tax Arbitrage.Bibliography.Index.
Includes bibliographical references (p. [407]) and index.
Keywords: Derivative securities -- United States; Options (Finance) -- United States